Development of natural rubber-bamboo biochar composites for vibration and noise control applications. (1st November 2022) - Sunali,; Mago, Jonty; Negi, Ashutosh; Pant, K.K.; Fatima, S.
Abstract: The present study focuses on the utilization of bamboo biochar (BB) as a filler in natural rubber (NR) composites. This work is the first attempt to investigate the influence of BB loading on the vibration damping and acoustical properties of NR composites. NR-BB composites were prepared according to the ASTM D3182-21a standard. Vibration damping and acoustical properties were examined using the Obrest beam (ASTM E756-05 ) and four microphone impedance tube (ASTM E2611-19 ) methods. Noteworthy, the vibration damping ratio or system loss factor (ξ) obtained maximum for the fourth mode of vibration (NR- ξ = 33.19, NR/10BB- ξ = 17.46, and NR/20BB- ξ = 13.50) in the free layer damping (FLD) configurations. However, the sound transmission loss (STL) was enhanced by 8% and 11% compared to NR composites upon adding 10 and 20 phr of BB, respectively. In addition to vibration damping and STL, the loading of BB in the NR matrix positively influenced physical, mechanical, and thermal properties. Graphical abstract: Image 1